2022
DOI: 10.1021/acs.inorgchem.2c00522
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycle-Induced Modulation of Internuclear Interactions in Homobimetallic Complexes

Abstract: A synthetic route has been developed for a series of 3d homobimetallic complexes of Mn, Fe, Co, Ni, and Cu using three different pyridyldiimine and pyridyldialdimine macrocyclic ligands with ring sizes of 18, 20, and 22 atoms. Crystallographic analyses indicate that while the distances between the metals can be modulated by the size of the macrocycle pocket, the flexibility in the alkyl linkers used to construct the macrocycles enables the ligand to adjust the orientation of the PD­(A)­I fragments in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 167 publications
(261 reference statements)
2
5
0
Order By: Relevance
“…distances, which diverge from the value of 2.873(1) Å for each interaction in 3 [Cu2Cl2] 2+ to values of 2.7273 and 3.021 Å in 2 [Cu2Cl2] 2+ . While these distances are long, they are well within the sum of the van der Waals radii for Cu and Cl (4.20 Å) [28], and previous work from our group on closely related molecules has identified magnetic communication through bridging chloride ligands with Cu-Cl distances up to 3.159(1) Å [21]. Aside from the noted differences in the Cu2Cl2 core, the remaining bond metrics of…”
Section: Ring-size Modulated Structures Of [Cu 2 CL 2 ] 2+ Cluster Coressupporting
confidence: 72%
See 1 more Smart Citation
“…distances, which diverge from the value of 2.873(1) Å for each interaction in 3 [Cu2Cl2] 2+ to values of 2.7273 and 3.021 Å in 2 [Cu2Cl2] 2+ . While these distances are long, they are well within the sum of the van der Waals radii for Cu and Cl (4.20 Å) [28], and previous work from our group on closely related molecules has identified magnetic communication through bridging chloride ligands with Cu-Cl distances up to 3.159(1) Å [21]. Aside from the noted differences in the Cu2Cl2 core, the remaining bond metrics of…”
Section: Ring-size Modulated Structures Of [Cu 2 CL 2 ] 2+ Cluster Coressupporting
confidence: 72%
“…The bis(pyridyldiimine) macrocyclic ligands have provided a useful platform to study multinuclear copper chemistry, but synthetic elaborations and structural information on these systems are limited. Previous work in our lab has shown that the syntheses of dinuclear first-row transition metal bis(pyridyldiimine) macrocyclic complexes were aided by the installation of tert-butyl groups at the 4-position of the PDI units [18][19][20][21][22][23][24][25]. The tert-butyl groups allow for an enhancement in solubility in less polar organic solvents (THF, DCM, and MeCN) compared to the original macrocycles reported by Drew and Nelson. We thus sought to synthesize a new series of Cu2(II,II) bis(pyridyldiimine) macrocycles for structural characterization.…”
Section: Introductionmentioning
confidence: 99%
“…The two unique Co–H distances are nearly identical at 1.5898 and 1.6048 Å, and the Co–Co distance is 2.5304(4) Å. The small bridging groups appear to displace the metal atoms from the PDI planes, and this is reflected in the distance between the plane created by the three PDI nitrogen atoms and the metal center, being 0.356 Å in [Co 2 H 2 ] 0 relative to 0.036 Å in [Co 2 (PMe 3 ) 2 ] 0 . Compared to the related [κ 2 -(NacNac)Co] 2 (μ-H) 2 ] complex reported by the Holland group and another dicobalt dihydride supported by an enamidophosphinimine ligand, the Co–H and Co–Co distances are consistent with literature precedent.…”
Section: Resultsmentioning
confidence: 79%
“…In this context, di- or multinuclear transition metal complexes supported by two or more PDI moieties have been developed by Li, Toti, Osakada, Sun, Jordan, and others, which have been studied in catalytic ethylene polymerization. In addition, Tomson and co-workers pioneered elegant studies on interesting structures of PDI-macrocyclic ligand-based binuclear metal complexes and their reactivities on small-molecule activation . Very recently, our group reported a stereodivergent semireduction of alkynes catalyzed by a dinuclear cobalt complex, providing both Z - and E -alkene products in good chemo- and stereoselectivities simply by adjusting the amount of H 2 O .…”
Section: Resultsmentioning
confidence: 99%